Customer perception towards traditional taxi services in Klang valley / Noor Amirah Ab Rahman, Nur Izzati Syazwani Ghazali and Wan Nor Syazleen Wan Ismail - Ab Rahman, Noor Amirah; Ghazali, Nur Izzati Syazwani; Wan Ismail, Wan Nor Syazleen (2019)
Taxi services in Malaysia have negative image with the passengers because of poor conduct by local taxi drivers such as refusing to use taximeters, fleecing passengers, rudeness with customers, choosing preferred destinations and driving poor maintained taxis. Malaysian taxi services had severely marred our country’s reputation by being ranked as the worst taxi service around the globe. This kind of news can give a bad perception to potential customers as well. In addition, the entering of e-hailing industry in Malaysia also build a big competition to traditional taxi industry in Malaysia. In this research, SERVQUAL Model such as tangibility, reliability, responsiveness, assurance and empathy can influence customer perception towards traditional taxi services in Klang Valley. A good taxi service will give a good perception towards customer, thus, can enhance customer loyalty. This research examines the customer perception towards traditional taxi services in Klang Valley to see the relevance of taxi services nowadays. This study is based on data obtained from 250 survey questionnaires through self-administered that polled customer perception towards the service quality of the traditional taxi services. Finding of this study shows that tangibility, reliability, responsiveness and empathy have significant influence on customer perception towards traditional taxi services in Klang Valley. However, this study found that assurance has no significant influence on customer perception. The results of this study also suggested that a SWOT TOWS strategic approach is needed for the traditional taxi to enhance the customer perception. Recommendations are made to improve the traditional taxi services. This finding can help practitioners to understand how tangibility, reliability, responsiveness, assurance and empathy of traditional taxi services can be further improved to enhance customer perception. It is hoped that this study can contribute to the improvement of traditional taxi services in Klang Valley.